To Care for or to Care about? Justice and Injustices in Commodified Care Work - Laura Brito (e-cadernos ces)
In Portugal, cooperation between the state and non-governmental organisations has led to the creation of institutions that provide care services, called IPSS [Private Institutions of Social Solidarity]. This paper presents the results of an ethnography carried out in a rural IPSS that provides care for the elderly. The fieldwork aimed to understand how claims for justice are negotiated between care workers, care users and employers. The objective of this paper is to contribute to the debate on redistributive justice by showing how inequality of income affects access to care as well as examining the idea of justice as a lived experience by demonstrating how claims for justice are depicted in day-by-day relationships of care. This paper is divided into two parts, the first being an introduction contextualising Portuguese care work. The second part focuses on António’s story and reflects upon the work of two caregivers and their claim for justice.